2021
DOI: 10.7554/elife.66466
|View full text |Cite
|
Sign up to set email alerts
|

The genetic organization of longitudinal subcortical volumetric change is stable throughout the lifespan

Abstract: Development and aging of the cerebral cortex show similar topographic organization and are governed by the same genes. It is unclear whether the same is true for subcortical regions, which follow fundamentally different ontogenetic and phylogenetic principles. We tested the hypothesis that genetically governed neurodevelopmental processes can be traced throughout life by assessing to which degree brain regions that develop together continue to change together through life. Analyzing over 6000 longitudinal MRIs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 75 publications
(101 reference statements)
0
6
0
Order By: Relevance
“…Despite the pleiotropic effects, concordance of effects was generally null. This is not surprising, as rate-of-change measures for brain structures are not constant and often switch sign over the course of the lifespan 1 , 39 , whereas the GWAS for other traits assume stability of both the phenotype and the genetic influences on the phenotype over time. As such, concordance and discordance of effects would not be expected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the pleiotropic effects, concordance of effects was generally null. This is not surprising, as rate-of-change measures for brain structures are not constant and often switch sign over the course of the lifespan 1 , 39 , whereas the GWAS for other traits assume stability of both the phenotype and the genetic influences on the phenotype over time. As such, concordance and discordance of effects would not be expected.…”
Section: Discussionmentioning
confidence: 99%
“…This approach allowed us to find brain-structure-specific associations. However, several longitudinal studies have described phenotypic correlations between structural changes 39 , 47 , 48 ; combining several phenotypes could thus be an alternative approach to identify genetic variants that exert a global effect. Of note, cohort and age are intertwined in our meta-regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The observed heterogeneity in atrophy profiles may relate to evidence that the genetic influences on atrophy rates differ for cortex, hippocampus, and the caudate ( Fjell et al. 2021 ; Brouwer et al.…”
Section: Discussionmentioning
confidence: 99%
“…2020 ). Additional genes with distinct influences on the caudate relative to hippocampus and cortex likely also play a role ( Fjell et al. 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that changes of cortical thickness covariances in both development and ageing were closely correlated with the genetic organisation (Fjell et al, 2015), and subcortical structures were also governed by the same sets of genes (Fjell et al, 2021). It would be interesting to explore whether cortical thickness and subcortical covariances are associated with longevity by examining relevant genes of longevity polygenic risk scores (longevity-PRS) (Dong et al, 2022; Tesi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%